Finite Time Stabilization of the Four Tanks System: Extensions to the Uncertain Systems - Chakib Ben Njima; Walid Ben Mabrouk; Hassani Messaoud; Germain Garcia (Abstract and Applied Analysis)
We consider the finite time stability and stabilization of linear systems described in continuous time. First, we provide a condition for the stability over time using the state transition matrix standard. Then we give conditions to design a state feedback control that stabilizes the system over time. In some cases where there is uncertainty in the system model, the previous conditions are extended to a certain class of uncertain systems. The considered uncertainties are the polytopic and norm bounded ones. To reveal the proposed approach, an application to the four tanks system was made.